Tracking critical power using maximal mean power outputs during short, medium, and long intervals in well-trained cyclists - Galan-Rioja, M. A.; Gonzalez-Mohino, F.; Sanders, D.; Spragg, J.; Gonzalez-Rave, J. M. (Medicina dello Sport, 2022)
BACKGROUND: The determination of critical power (CP) during training is a useful tool monitoring performance progression and to demarcate training intensity zones. The aims of this study were: 1) to compare CP with varied effort short, medium and long intervals (SML-INT) with a field CP test; 2) to assess if SML-INT is an effective way to improve CP.